2016
DOI: 10.1089/rej.2015.1703
|View full text |Cite
|
Sign up to set email alerts
|

2-Arachidonylglycerol Protects Primary Astrocytes Exposed to Oxygen-Glucose Deprivation Through a Blockade of NDRG2 Signaling and STAT3 Phosphorylation

Abstract: The human N-Myc downstream-regulated gene 2 (NDRG2) is expressed in astrocytes, and may be involved in the modulation of gliacyte function in the central nervous system. Our previous study found suppression of NDRG2 up-regulation in reactive astrocytes in cerebral ischemic tolerance. 2-Arachidonylglycerol (2-AG) can induce cerebral ischemic tolerance. However, the underlying mechanism of NDRG2 in cytoprotection induced by 2-AG in primary astrocytesis still unknown. In this study, we investigated the role of ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…2-AG also seems to reduce the astrocytic production of chondroitin sulfate proteoglycan, that accumulates in MS lesions and is thought to be linked to the failure to regenerate, impeding oligodendrocyte precursor cell differentiation, and neuronal growth [ 154 ]. Moreover, 2-AG protects astrocytes exposed to oxygen-glucose deprivation through a blockade of NDRG2 signaling and STAT3 phosphorylation [ 155 ]. 2-AG and PEA have been shown to attenuate amyloid β-induced astrocyte activation and PEA increased 2-AG production in astrocytes [ 156 , 157 , 158 ].…”
Section: Neuroinflammation-induced Synaptopathy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…2-AG also seems to reduce the astrocytic production of chondroitin sulfate proteoglycan, that accumulates in MS lesions and is thought to be linked to the failure to regenerate, impeding oligodendrocyte precursor cell differentiation, and neuronal growth [ 154 ]. Moreover, 2-AG protects astrocytes exposed to oxygen-glucose deprivation through a blockade of NDRG2 signaling and STAT3 phosphorylation [ 155 ]. 2-AG and PEA have been shown to attenuate amyloid β-induced astrocyte activation and PEA increased 2-AG production in astrocytes [ 156 , 157 , 158 ].…”
Section: Neuroinflammation-induced Synaptopathy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In this study, we discovered that NDRG2 promoted the expression of p-STAT3, and STAT3 knockdown attenuated the antiapoptotic effect of NDRG2 in photoreceptors. Although the NDRG2-mediated promotion of p-STAT3 expression has been reported in astrocytes, the specific molecular mechanism remains unclear [36,37]. Previous studies have demonstrated that NDRG2 exerts regulatory control over the expression of cytokines, including interleukin-6 (IL-6), IL-1b, IL-10, and the leukocyte inhibitory factor [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing JAK2/STAT3 phosphorylation can decrease neuronal death, narrow infarct size and prevent post-ischemic damage of nerve cells. Wang et al reported a significant neuroprotective effect by reducing the phosphorylation of STAT3 following cerebral ischemia through RNA interference (38). Others have found that electroacupuncture stimulation of focal cerebral ischemia at the Baihui acupoint and Dazhui acupoint in rats relieved nerve function deficit by reducing the expression of JAK2, preventing abnormal JAK2 activation and downregulating the phosphorylation of STAT3 (37).…”
Section: Discussionmentioning
confidence: 99%